Réponses

2013-12-26T16:33:12+01:00
(3a-2)(4a-7)
12a²-21a-8a+14=12a²-29a+14
(2b-3)(2b-7)
4b²-14b-6b+21=4b²-20b+21
(3x-4)(5x+2)
15x²+6x-20x-8=15x²-14x-8
(-a+5b)(4b+3a)
-4ab-3a²+20b²+15ab=-3a²+20b²+11ab

-(3+a)=-3-a
-(-5-x)=5+x
-(-6-4a)=6+4a
-(2x+4)=-2x-4
2013-12-26T17:21:37+01:00
Développer et réduire les expressions

(3a-2)(4a-7)
=12a²-21a-8a+14
=12a²-29a+14

(2b-3)(2b-7)
=4b²-14b-6b+21
=4b²-20b+21

(3x-4)(5x+2)
=15x²+6x-20x-8
=15x²-14x-8

(-a+5b)(4b+3a)
=-4ab-3a²+20b²+15ab
=-3a²+20b²+11ab

écrire sans parenthèses chaque expression

-(3+a)
=-3-a

-(-5-x)
=5+x

-(-6-4a)
=6+4a

-(2x+4)
=-2x-4